The «Rebus Sic Stantibus» Clause and its Application to Contracts in Crisis Situations: The Challenges of its Normative Regulation (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
The Rebus Sic Stantibus clause is deemed a repair mechanism of the contract which, due to a sudden and unforeseeable change in circumstances, has experienced damage in its performance balance during its conclusion. The crisis caused by the COVID-19 global pandemic brings about questions regarding this matter, such as the feasibility of its application amongst the litigations present during the last months, as well as its potential regulation. This paper will analyse any certainties and uncertainties on this topic.
Keywords: rebus sic stantibus; COVID-19; regulation